"I have the highest GPA, but I can't be the valedictorian?": two Black males' exclusionary valedictory experiences. Issue 2 (23rd February 2022) - Jett, Christopher C.
ABSTRACT: Being the valedictorian is the highest honor bestowed upon a senior. Unfortunately, that was not the case for Jeffrey and Autry, the two high-achieving African American male participants in this critical race qualitative study, who were short-changed of their valedictorian status. Their cases reveal three themes: (1) these Black male students were shocked they did not receive this honor and were exploited in the process, (2) there were unfair institutional policies and practices associated with this title, and (3) there were drastic differences regarding the academic expectations for other students who were vying for this valedictory designation. Therefore, these African American male students experienced this academic honor as an exclusionary enterprise. Implications for practitioners, policymakers, and researchers are shared to mitigate the barriers associated with the valedictory accolade.